Perancangan Backend Api Berbasis Rest-Api pada Aplikasi Rekomendasi Resep Makanan - Agil Maulana Nanda Riady; Paniran Paniran; I Made Budi Suksmadana (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
This study explores the design intricacies of a scalable RESTful Backend API tailored for a sophisticated food recipe recommendation application, with a primary focus on leveraging the Google Cloud Platform (GCP) for deployment. Employing a service-oriented paradigm, the API segregates Backend functionalities, fostering optimal scalability. The REST architecture ensures seamless integration, while GCP guarantees reliability and scalability. Utilizing Node.js and Express.js, the API efficiently manages culinary recipes and user preferences. Rigorous performance evaluations affirm its rapid responsiveness. This paper offers pragmatic guidelines for developers, emphasizing the significance of GCP for seamless and scalable deployments.